NMR observation of water transfer between a cement paste and a porous medium. (May 2017) - Fourmentin, M.; Faure, P.; Rodts, S.; Peter, U.; Lesueur, D.; Daviller, D.; Coussot, P.
Abstract: We show that it is possible to follow the liquid transfer between a cement paste and a porous medium in contact with it, by analysing the evolution of the distribution of 1 H NMR relaxation times. This in particular makes it possible to see that whatever the initial water fraction in the paste, a porous medium with sufficiently small pores can rapidly extract a significant amount of water from this paste. Afterwards, during the hydration process, the cement paste progressively gets water back from this porous medium. The amount of water thus extracted by the paste finally appears to just compensate the volume loss due to water consumption by the hydration process.